Drivers of brand loyalty in the chain coffee shop industry - Han, Heesup; Hong, Ngoc Nguyen; Song, Hakjun; Chua, Bee Lia; Lee, Sanghyeop; Kim, Wansoo (Elsevier, 2018)
The present study aimed to examine patrons’ loyalty generation process for a chain coffee shop brand by considering the role of cognitive drivers, affective drivers, brand satisfaction, and relationship commitment. A field survey was conducted in chain coffee shops located in the popular shopping districts of a metropolitan city in South Korea. The proposed model was evaluated by using a structural equation analysis. The results revealed that cognitive and affective factors were in general significantly interrelated; such associations along with brand satisfaction and relationship commitment significantly influenced brand loyalty; and, the brand satisfaction was the most important contributor to building brand loyalty. In addition, the mediating role of study variables was identified. Overall, the proposed theoretical framework contained a sufficient level of explanatory power for brand loyalty. With a lack of research about coffee shop customers’ purchasing behavior, the findings can be meaningfully used for the enhancement of customer loyalty.